Organizing Muslims and Integrating Islam in Germany: New Developments in the 21st Century - Rosenow-Williams, Kerstin (Muslim Minorities, 2012)
In Organizing Muslims and Integrating Islam in Germany, Kerstin Rosenow-Williams analyzes the challenges faced by Islamic organizations in Germany since the beginning of the 21st century, providing original empirical insights based on an innovative sociological research perspective